Upper miocene planktonic foraminifera from Algarve. Chronostratigraphical implications - Legoinha, P. (Departamento de Ciências da Terra, 2003)
New data on the planktonic foraminifera from the Upper Miocene Cacela Formation and Mem Moniz spongoliths are presented. The coiling type of Globorotalia menardii from Cacela and Quelfes and the occurrence at Quelfes of G. miotumida allow correlation with the bio-events I to 3 (7,512 to 7,24 Ma; Sierro et al., 1993; 2001) that have been recognized in the Guadalquivir Basin (Spain). The presence of Neogloboquadrina acostaensis and N. humerosa at Mem Moniz points out to the Upper Miocene (Tortonian, upper N16, or even NI7). Mem Moniz spongoliths are correlated with the Cacela Formation. Some 87Sr/86Sr isotopic ages of mollusc or foraminifera shells don't fit well with finer biostratigraphic record and present wide error margins.